Pengaruh Kemampuan Numerik terhadap Hasil Belajar Matematika Siswa Kelas VII SMP Negeri 10 Yogyakarta - Fitriyani Handayani; Widayati, Widayati (Lembaga Pengembangan Kinerja Dosen, 2025)
The phenomenon of low numerical ability and persistent obstacles to student learning outcomes. The objectives of this study are: (1) To determine the influence of the level of numerical ability of seventh-grade students at SMP Negeri 10 Yogyakarta, (2) To determine the influence of the magnitude of the mathematics learning outcomes of seventh-grade students at SMP Negeri 10 Yogyakarta, and (3) To find the influence of numerical ability on the learning outcomes of seventh-grade students at SMP Negeri 10 Yogyakarta. This type of research is quantitative correlational. The subjects of this study were seventh-grade students, whose numerical ability and mathematics learning outcomes were the objects of this research. Data collection methods used were a numerical ability test and a mathematics learning outcome test on the topic of social arithmetic. The research instruments used were essay-style numerical ability worksheets and multiple-choice social arithmetic worksheets. Data analysis methods used prerequisite tests (linearity test, normality test, and homogeneity test) and simple linear regression analysis.This study yielded the following findings: (1) The overall level of numerical ability of students in class VIII D of SMP Negeri 10 Yogyakarta is in the moderate category, (2) The level of mathematics learning outcomes for the topic of arithmetic of students in class VII D of SMP Negeri 10 Yogyakarta is in the moderate category, and (3) There is a positive and significant influence between numerical ability and students' mathematics learning outcomes. This is evidenced by the correlation coefficient value of 0.845 and the coefficient of determination (R square) which shows that numerical ability contributes 71.4% to students' mathematics learning outcomes.